Mesonephric adenocarcinoma (endometrioid type) of endocervix with diffuse mesonephric hyperplasia involving cervical wall and myometrium: An unusual case report - Santosh Menon; Komal Kathuria; Kedar Deodhar; Rajendra Kerkar (Wolters Kluwer Medknow Publications, 2013)
Malignant mesonephric tumors are rare variants of cervical adenocarcinoma, derived from remnants of mesonephric ducts and are associated with mesonephric remnants and/or mesonephric hyperplasia. Few cases have been described in literature. We report an unusual case of cervical mesonephric adenocarcinoma of endometrioid type with squamous morules in association with diffuse mesonephric hyperplasia involving the cervical walls and extending into the myometrium.